The Impact of Early Epidural Analgesia on the Course of Labor and Delivery - Atene Simanauskaite; Gabriele Kavaliauskaite; Justina Kacerauskiene; Vilda Vilimiene (Medicina)
Background and Objectives: This study aimed to assess the impact of early epidural analgesia (EA) on the progression of labor and delivery outcomes among nulliparous women. Materials and Methods: A retrospective analysis was conducted utilizing data from the Birth Registry of the Department of Obstetrics and Gynecology at LUHS. The dataset encompassed women who underwent childbirth between 1 January 2021 and 31 December 2021 and who received EA for labor pain management. A total of 89 women with low-risk deliveries and EA were included in the study. The cohort was divided into two groups: Group I—parturients who underwent early EA with cervical dilatation ≤3 cm—and Group II—parturients who underwent EA with cervical dilatation >3 cm but <7 cm. The results were processed using IBM SPSS. Results: Group I consisted of 25 (28.1%) women and Group II consisted of 64 (71.9%). The prevalence of obesity was higher in Group II (p = 0.021). Bishop score was statistically elevated in Group II (p = 0.018). Upon hospital admission, Group II exhibited greater cervical dilation (p = 0.001). The rate of cervical dilation was higher in Group II at 1.54 cm/h (p = 0.033). Episiotomy was more frequently performed in Group II (p = 0.014). The average durations of the first stage of labor (p = 0.045), the second stage of labor (p = 0.033), and the overall labor (p = 0.023) were prolonged in Group I. Conclusions: The cervical dilation up to 10 cm occurs at a swifter pace when EA is administered following cervical dilation exceeding 3 cm. Notable associations were observed between EA and the incidence of episiotomy as well as the duration of labor stages. Early EA exhibited no impact on neonatal outcomes.